AIR TRANSPORT ACCESSIBILITY AND TRANSPORT DISCRIMINATION OF POPULATION IN CONSTITUENTS OF THE RUSSIAN FEDERATION - S. F. Egoshin; A. V. Smirnov (Научный вестник МГТУ ГА, 2018)
The article deals with the introduction of numerical indicators for the notions "the air transport accessibility" and "the transport discrimination of the population" as applied to the local (suburban) traffic. Due to significant financial cost of air service, the local airlines are essential only in those regions of the Russian Federation, where the low-cost ground traffic is impossible. Thereby, the air transport accessibility should be considered as paired accessibility "the regional center - the capital of the constituent of the Russian Federation". This fact imposes restrictions on those indicators that can be applied to the relevant numerical estimates. A technique has been developed for numerical estimation of transport accessibility and transport discrimination of the population using the notions "transport accessibility levels" and "minimum social transport standard". The results of calculations with a software package based on geoinformation system are presented. It is shown that when using only the ground transport, the capital transport accessibility level of the constituent of the Russian Federation exceeds four hours for residents including more than 450 municipal and urban districts in 50 constituents of the Russian Federation. The most of these territorial entities belong to the hard-to-reach territories of Northwestern, Ural, Siberian and Far Eastern Federal Districts of Russia. The total population of these entities is about 15 million people, which is more than 10% of the total population of Russia. The existing local airlines can solve the transportation problems in local traffic for about 5 million people. To ensure four-hour level of transport accessibility for the rest of the population, it is necessary to organize at least 300 local airlines in the constituents of the Russian Federation.